EKSISTENSI SISTEM HUKUM PERIZINAN KEGIATAN PERTAMBANGAN DALAM OTONOMI DAERAH SEBAGAI SALAH SATU INSTRUMEN HUKUM PENJAMIN AL-IMARAH: Jurnal Pemerintahan dan Politik Islam Vol. 2, No. 1, 2017 HAK-HAK MASYARAKAT - David Aprizon Putra (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
Abstract: Mining activity permit system would be the most urgent and most of its functions in maintaining the implementation of processing and environmental protection in Indonesia. Moreover, of course, is the role of Government and Local Government as the host. The ultimate goal of this course is for the benefit of mankind itself, the interests of society. How far this permit system is able to maintain the rights of communitities in generally and affected communities in especially, how strong is the licensing system is able to accommodate the interests and rights of the communities. What is the quality permits issued by local governments in terms of maintaining the rights of its people.Keywords: law system, mining activity, rights of people